Peripheral Blood Inflammatory Biomarkers Reflect Glioma Malignancy Grade: A Single-Center Study - Naura Salma Ramadhani; Djohan Ardiansyah; Ferdy Royland Marpaung (Universitas Airlangga, 2026)
Highlight: Glioma represents the most prevalent form of malignant brain tumor, displaying a spectrum of grades. The dNLR shows a significant correlation with glioma grade. Inflammatory biomarkers could facilitate the early prediction of glioma aggressiveness. ABSTRACT Introduction: Gliomas are the most prevalent primary tumors of the central nervous system with varying degrees of aggressiveness and prognoses. Peripheral blood inflammatory markers, including the neutrophil-to-lymphocyte ratio (NLR), the derived neutrophil-to-lymphocyte ratio (dNLR), the platelet-to-lymphocyte ratio (PLR), and the lymphocyte-to-monocyte ratio (LMR), have been proposed as prognostic indicators for tumors. Inflammation is a major factor in tumor progression. Objective: To identify peripheral inflammatory markers correlated with glioma grade and assess their potential as non-invasive, cost-effective tools for clinical decision-making. Methods: This retrospective observational study reviewed the medical records of 144 patients with histopathologically confirmed gliomas treated at Dr. Soetomo General Hospital, Surabaya, between 2019 and 2024. Preoperative peripheral blood inflammatory markers obtained 24–72 hours before neurosurgical intervention were analyzed using Spearman correlation and non-parametric group comparison tests to evaluate their association with glioma grade according to the 2021 WHO criteria. Results: The trends of NLR, PLR, and LMR were as expected but statistically insignificant. Statistical analysis showed that elevated dNLR values ​​were significantly associated with higher glioma grade (p < 0.001). Conclusion: dNLR is an important inflammatory marker associated with glioma malignancy, suggesting its potential clinical utility for predicting disease severity and patient outcomes.